The effects of subordinates' performance on manager-subordinate conflict conflict under the moderation effect of propensity to trust: An attribution approach - ATAMAN BERK, GÖKSEL (My University, 2022)
Purpose This study aims to reveal the role of performance on the likelihood of conflict occurrence and the conditions that affect this relationship. This study measures managers\" perceptions about the cause of the subordinate\"s low-level performance, stability of the performance, propensity to trust of managers and investigate the effects of them on conflict types. Design/methodology/approach This study draws on the attribution theory for investigating the effect of the negative performance of subordinates on a conflict between manager and subordinate by using the quantitative research method. A random sample was drawn from 150 Turkish mid-level managers from midsized small and medium - sized enterprises companies. The hypotheses are tested by hierarchical linear modeling. Findings According to results, negative performance of subordinates may predict the types of conflict depending on the attributions of managers about negative performance. In addition, the manager\"s attributions to the locus of control or/and to the stability affect the likelihood of conflict types occurrence, between managers and subordinates. Depending on the managers\" attributions, the propensity to trust of managers has a significant moderation effect on the relationship between performance of subordinates and the likelihood of conflict types occurrence. Originality/value This study advances knowledge on conditions that affect the likelihood of conflict occurrence. It contributes to the literature by suggesting performance as a predictor of conflict instead of an outcome of the conflict. The research is one of the rare studies investigating the relationship between attributions and conflict. In addition, it expands the understanding of personal traits and conflict interaction by testing the moderation effect of propensity to trust.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Bilim, Teknoloji ve Toplum; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Sociology; Science, Technology and Society; Labor Economics and Industrial Relations; Management and Industrial Psychology; Mass Communications and Mass Media; İLETİŞİM; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); YÖNETİM; Ekonomi ve İş; SİYASET BİLİMİ; COMMUNICATION; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); MANAGEMENT; ECONOMICS & BUSINESS; POLITICAL SCIENCE; General Decision Sciences; Political Science and International Relations; Decision Sciences (miscellaneous); General Social Sciences; Communication; Social Sciences & Humanities; Employee performance; Propensity to trust; Attribution theory; Relationship conflict; Task conflict; Manager-subordinate conflict; CAUSAL DIMENSION SCALE; ORGANIZATIONAL CONFLICT; TASK CONFLICT; INTRAGROUP CONFLICT; GENERALIZED EXPECTANCIES; RELATIONAL ATTRIBUTIONS; PERSONALITY-TRAITS; BOUNDARY-CONDITION; TEAM PERFORMANCE; PEER RESPONSES; Manager–subordinate conflict; Employee performance; Propensity to trust; Attribution theory; Relationship conflict; Task conflict; Manager–subordinate conflict